EFL TEACHERS’ EMOTIONS ABOUT USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN UNIVERSITY CONTEXT: A QUALITATIVE STUDY - Thi Thu Trang, Dinh; Hai Ha, Nguyen (HNUE Journal of Science: Journal of Educational Science, 2025)
As Artificial Intelligence (AI) technologies become increasingly integrated into education, teachers encounter new opportunities and challenges that influence their professional practices and provoke a wide range of emotional responses. Employing the Control-Value Theory (CVT) and in-depth interviews, this study explores the emotional experiences of 10 English as a Foreign Language (EFL) teachers of a public university in Vietnam who use AI technologies in their teaching. The participants expressed excitement about AI’s potential support for teaching and research but showed doubts about its limitations and concerns regarding the impacts on students, classroom interactions and academic integrity. They also experienced frustration with the lack of institutional support but conveyed a boosted sense of confidence in their irreplaceable human expertise. These mixed findings largely align with previous studies on the integration of AI-powered tools in education, support the applicability of CVT for investigating teacher emotions and extend the discussion on the affective dimension of AI-assisted EFL instruction. Although limited by the small sample size, this study contributes to advancing knowledge about the complexity of teacher emotions and calls for more comprehensive support systems to facilitate teachers in managing the pedagogical and emotional demands of AI integration.